Sex‐specific control of central nervous system autoimmunity by p38 mitogen‐activated protein kinase signaling in myeloid cells. Issue 1 (January 2014) - Krementsov, Dimitry N.; Noubade, Rajkumar; Dragon, Julie A.; Otsu, Kinya; Rincon, Mercedes; Teuscher, Cory
<x xml:space="preserve">Abstract</x> Objective Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system (CNS), characterized by a global increasing incidence driven by relapsing–remitting disease in females. Investigators have described p38 mitogen‐activated protein kinase (MAPK) as a key regulator of inflammatory responses in autoimmunity, but its role in the sexual dimorphism in MS or MS models remains unexplored. Methods Toward this end, we used experimental autoimmune encephalomyelitis (EAE), the principal animal model of MS, combined with pharmacologic and genetic inhibition of p38 MAPK activity and transcriptomic analyses. Results Pharmacologic inhibition of p38 MAPK selectively ameliorated EAE in female mice. Conditional deletion studies demonstrated that p38α signaling in macrophages/myeloid cells, but not T cells or dendritic cells, mediated this sexual dimorphism, which was dependent on the presence of adult sex hormones. Analysis of CNS inflammatory infiltrates showed that female but not male mice lacking p38α in myeloid cells exhibited reduced immune cell activation compared with controls, whereas peripheral T‐cell priming was unaffected in both sexes. Transcriptomic analyses of myeloid cells revealed differences in p38α‐controlled transcripts comprising female‐ and male‐specific gene modules, with greater p38α dependence of proinflammatory gene expression in females. Interpretation Our findings demonstrate a key role for p38α in myeloid cells in CNS autoimmunity and uncover important molecular mechanisms underlying sex differences in disease pathogenesis. Taken together, our results suggest that the p38 MAPK signaling pathway represents a novel target for much needed disease‐modifying therapies for MS. Ann Neurol 2014;75:50–66